2020
DOI: 10.3390/ijms21228708
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Anthocyanins-Related Glutathione S-Transferase (GST) Genes in the Genome of Cultivated Strawberry (Fragaria × ananassa)

Abstract: Anthocyanins are responsible for the red color of strawberry, they are a subclass of flavonoids synthesized in cytosol and transferred to vacuole to form the visible color. Previous studies in model and ornamental plants indicated members of the glutathione S-transferase (GST) gene family were involved in vacuolar accumulation of anthocyanins. In the present study, a total of 130 FaGST genes were identified in the genome of cultivated strawberry (Fragaria × ananassa), which were unevenly distributed across the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 61 publications
2
15
0
Order By: Relevance
“…The PcGST family was divided into 10 subfamilies, including lambda (L), dehydroascorbate reductase (DHAR), metaxin (M), tetrachlorohydroquinone dehalogenase-like (TCHQD), glutathionyl hydroquinone reductase (GHR), γ-subunit of the eukaryotic translation elongation factor 1B (EF1Bγ), Zeta (Z), Theta (T), Phi (F), and Tau (U). These were consistent with the GST subfamily in other species, including tomato, strawberry, and apple [ 21 , 28 , 36 ]. Among these subfamilies, the Tau subfamily contained the most PcGST genes (24), accounting for more than half of the total PcGST genes, followed by 11 PcGST genes in the Phi subfamily.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…The PcGST family was divided into 10 subfamilies, including lambda (L), dehydroascorbate reductase (DHAR), metaxin (M), tetrachlorohydroquinone dehalogenase-like (TCHQD), glutathionyl hydroquinone reductase (GHR), γ-subunit of the eukaryotic translation elongation factor 1B (EF1Bγ), Zeta (Z), Theta (T), Phi (F), and Tau (U). These were consistent with the GST subfamily in other species, including tomato, strawberry, and apple [ 21 , 28 , 36 ]. Among these subfamilies, the Tau subfamily contained the most PcGST genes (24), accounting for more than half of the total PcGST genes, followed by 11 PcGST genes in the Phi subfamily.…”
Section: Resultssupporting
confidence: 85%
“…Initially, only three GST subfamilies were identified, including Theta, Tau, and Zeta [ 43 ]. Subsequently, the GST gene family was systematically and comprehensively analyzed, and increasing GST members were identified in various plant species, including maize [ 42 ], soybean [ 44 ], Arabidopsis [ 45 ], apple [ 36 ], strawberry [ 21 ], tomato [ 28 ], Citrus sinensis [ 46 ], kiwifruit [ 47 ], cotton [ 19 ], radish [ 22 ], wheat [ 48 ], and pepper [ 49 ]. The number of GST family members and the number of subfamilies vary in different plant species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of FaUBC genes is far more than the 45, 48, 52, 75, and 74 UBC genes isolated from the genome of Arabidopsis [ 32 ], rice [ 5 ], tomato [ 6 ], banana [ 7 ] and maize [ 33 ], which indicates that the UBC family expanded in strawberry. Gene duplication events such as whole genome duplication, tandem duplication, segmental duplication, and transposition have a remarkable role in the expansion of gene family members in genomes [ 34 ], and increasing evidences has shown that whole genome duplication are largely responsible for the expansion of gene families in cultivated strawberry, such as the GST, GMP and RALF gene families [ 35 37 ]. Additionally, the genome sizes of Arabidopsis, strawberry, rice, tomato, maize, and banana are ~ 125, ~ 240, ~ 466, ~ 466, ~ 900, ~ 2300, and 523 Mb, respectively.…”
Section: Discussionmentioning
confidence: 99%